Higher-Order Thinking Abilities for Improved Critical Thinking in Thermochemical Materials Module - Aida Auliyani; Abdul Gani*; Adlim Adlim (Universitas Pendidikan Ganesha, 2022)
The use of teaching materials that support higher-order thinking skills (HOTS) on thermochemical materials still needs to be improved, which makes students' critical thinking skills (CBC) low. The goal of this study is to find out if HOTS-based chemistry learning modules on thermochemical materials and improving CBC are possible and what students think of them when they are used. This study is a type of development research called